Pharmacokinetics and tolerability of SRT2104, a first‐in‐class small molecule activator of SIRT1, after single and repeated oral administration in man. (14th December 2012) - Hoffmann, Ethan; Wald, Jeff; Lavu, Siva; Roberts, John; Beaumont, Claire; Haddad, Jon; Elliott, Peter; Westphal, Christoph; Jacobson, Eric
<x xml:space="preserve">Abstract</x> Aim SRT2104 is a novel, first‐in‐class, highly selective small molecule activator of the NAD + dependent deacetylase SIRT1. SRT2104 was dosed to healthy male and female volunteers in a series of phase 1 clinical studies that were designed to elucidate tolerability and pharmacokinetics associated with oral dosing to aid in dose selection for subsequent clinical trials. Methods In the first‐in‐human study, there was both a single dose phase and 7 day repeat dose phase. Doses used ranged from 0.03 to 3.0 g. A radioactive microtracer study was subsequently conducted to determine systemic clearance, bioavailability and preliminary metabolism, and a crossover study was conducted to determine the effect of gender, formulation and feeding state on SRT2104 pharmacokinetics. Results SRT2104 was well tolerated in all of these studies, with no serious adverse reactions observed. SRT2104 displayed a dose‐dependent, but sub‐proportional increase in exposure following single dose and repeated dose administration. Accumulation of three‐fold or less occurs after 7 days of repeat dosing. The mean bioavailability was circa 14% and the mean clearance was circa 400 ml min−1. Although there were no substantial effects on exposure resulting from gender or formulation differences, a notable food effect was observed, manifested as up to four‐fold increase in exposure parameters. Conclusions In the absence of an optimized formulation of SRT2104, the food effect can be used to maximize exposure in future clinical studies. Combined with the good tolerability of all doses demonstrated in these studies, the favourable selectivity profile of SRT2104 allows for the use of this SIRT1 modulator for target validation in the clinic.